The Pancasila State As Darul Ahi Wa Shahadah From The Perspective Of National Psychology And Digital Adaptation - Sinta Luckyedi; Muh Nurhakim; Nanta Sigit (International journal of technology and education research, 2026)
This study examines the concept of Pancasila as Darul Ahdi wa Syahadah from the perspective of national psychology and digital adaptation. The rapid development of digital technology has significantly transformed social interactions, communication patterns, and identity formation, particularly among younger generations. While digitalization provides opportunities for broader participation and access to information, it also presents challenges such as misinformation, polarization, and the weakening of national values. In this context, strengthening national identity becomes an important issue that requires an interdisciplinary approach. This research employs a qualitative method with a descriptive-analytical approach. Data were collected through in-depth interviews, observations, and documentation studies involving students, educators, and community members who actively engage in digital environments. The data were analyzed using thematic analysis, including data reduction, data display, and conclusion drawing. The study integrates perspectives from ideology, Islamic thought, social psychology, and digital sociology to provide a comprehensive understanding of the research problem. The findings indicate that although individuals generally understand the basic values of Pancasila, their implementation in digital behavior remains inconsistent. The concept of Darul Ahdi wa Syahadah is implicitly reflected in participants’ perceptions but has not been fully realized in active forms of digital citizenship. Digital adaptation is found to have a dual impact, as it can both strengthen and weaken national identity depending on how individuals engage with digital media. Therefore, this study concludes that strengthening national psychology in the digital era requires not only cognitive understanding but also active and participatory engagement in embodying national values. This study contributes theoretically by integrating the concepts of Pancasila, Darul Ahdi wa Syahadah, and national psychology within the context of digital transformation. Practically, it offers insights for education, policy, and society in fostering a more adaptive and value-based national identity in the digital age.